A family of powerful halogen-bond donors: a structural and theoretical analysis of triply activated 3-iodo-1-phenylprop-2-yn-1-ones. Issue 4 (4th January 2022) - Panikkattu, Vinu V.; Sinha, Abhijeet S.; Aakeröy, Christer B.
Abstract : A new group of powerful halogen-bond donors have been synthesized and evaluated using structural and computational tools. Abstract : Strong halogen bonds can provide a foundation for reliable supramolecular strategies for effective self-assembly and design of functional materials. A new class of halogen-bond donors have been developed using structural and theoretical tools and these 3-iodo-1-phenylprop-2-yn-1-ones demonstrate several features that make them promising additions to the crystal engineering tool-box.